The Influence of Toxic Masculinity on Father Involvement in Parenting Among the Toba Batak Tribe - Sibagariang, Julia Lasmaroha; Siahaan, Ervina Marimbun Rosmaida (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This study aims to determine the Effect of Toxic Masculinity on Father Involvement in Parenting in the Toba Batak Tribe. From the results of research and data analysis conducted on Toba Batak fathers, the following conclusions can be drawn. The results of the study indicate that there is a significant negative influence between toxic masculinity and father involvement in parenting. This means that the stronger the values of toxic masculinity held by a father, the lower his involvement in childcare, both emotionally, physically, and communicatively. The majority of Toba Batak fathers in this study were in the moderate category in terms of involvement (father involvement), especially in the aspects of engagement and accessibility. However, involvement in the aspect of responsibility was relatively higher, which indicates that fathers tend to focus more on fulfilling economic needs than emotional closeness with children. Most respondents also had a moderate level of toxic masculinity, with the most dominant aspects being violence, misogyny, and greed. This indicates that traditional masculinity values still strongly influence the way fathers play their roles in the family.This study shows that the tendency towards toxic masculinity behavior contributes 20.7% to father involvement in parenting, while the remaining 79.3% is influenced by other factors.